Pengembangan Paradigma Pendidikan Holistik: Sinergi Kurikulum Berbasis Cinta dan Pembelajaran AI & Coding - Ridwan; Saiful Akmal; Cut Yety Kasturi (Jurnal Ilmiah Didaktika, 2026)
The rapid evolution of Artificial Intelligence (AI) and programming (coding) necessitates an innovative response from the educational sector to foster a generation that is not only digitally competent but also possesses strong character and ethics. This paper proposes a conceptual model to develop a holistic educational paradigm through the synergy between the Love-Based Curriculum (Kurikulum Berbasis Cinta or KBC) and AI & coding education within the madrasah environment. The objective is to bridge the gap between technological advancement and humanitarian values by establishing KBC as the ethical foundation for the development and utilization of technology. The methodology employed involves a literature analysis and synthesis to integrate the philosophical foundations of KBC, namely ontology, epistemology, and axiology, with the principles of AI ethics. The resulting model focuses on applying "Panca Cinta" (Five Loves) as an ethical framework for AI and coding projects, wherein students learn to create technological solutions that are humanistic, tolerant, and sustainable. The primary contribution of this paper is to offer a theoretical framework that serves as a basis for future empirical research and policy formulation by the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag). Consequently, madrasahs can act as pioneers in cultivating a superior generation that is not only digitally proficient but also empathetic, compassionate, and socially responsible in the global era.